2017
DOI: 10.1002/ece3.2709
|View full text |Cite
|
Sign up to set email alerts
|

Bigger is better: changes in body size explain a maternal effect of food on offspring disease resistance

Abstract: Maternal effects triggered by changes in the environment (e.g., nutrition or crowding) can influence the outcome of offspring–parasite interactions, with fitness consequences for the host and parasite. Outside of the classic example of antibody transfer in vertebrates, proximate mechanisms have been little studied, and thus, the adaptive significance of maternal effects on infection is not well resolved. We sought to determine why food‐stressed mothers give birth to offspring that show a low rate of infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
2
19
2
Order By: Relevance
“…The crustacean Daphnia magna exhibits clear maternal effects on size at birth and later performance traits (Ebert, ; Garbutt & Little, ; Lampert, ; Stjernman & Little, ; Tollrian, ): offspring of older mothers or those from calorie‐restricted mothers are larger and show enhanced resistance to pathogens than offspring of young or well‐fed mothers (Clark, Garbutt, McNally, & Little, ; Garbutt & Little, ). Almost half of offspring phenotypic variation (48%) in Daphnia pulex is due to maternal age (Plaistow, Shirley, Collin, Cornell, & Harney, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crustacean Daphnia magna exhibits clear maternal effects on size at birth and later performance traits (Ebert, ; Garbutt & Little, ; Lampert, ; Stjernman & Little, ; Tollrian, ): offspring of older mothers or those from calorie‐restricted mothers are larger and show enhanced resistance to pathogens than offspring of young or well‐fed mothers (Clark, Garbutt, McNally, & Little, ; Garbutt & Little, ). Almost half of offspring phenotypic variation (48%) in Daphnia pulex is due to maternal age (Plaistow, Shirley, Collin, Cornell, & Harney, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our aim was to dissect maternal effects and microRNA responses to environmental variation in the cyclically parthenogenetic crustacean Daphnia magna . We use D. magna for this purpose because it has clear maternal effect phenotypes in response to variation in food nutrition and age (Clark et al., ; Garbutt & Little, ). These strong maternal effects appear to be adaptive, and in the absence of genetic variation, we hypothesize they are controlled by a mixture of provisioning and epigenetic modifications, including miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…; Lorenz & Koella ; Stjernman & Little ; Tidbury et al . ; Boots & Roberts ; Garbutt & Little ). This suggests variation in phenotypic traits, as a response to the maternal environment, can drive population and epidemiological dynamics (Beckerman et al .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, maternal effects have been shown to affect population dynamics and demography through alterations in offspring reproduction, maturation and growth rate (Gaillard et al 2003;Benton et al 2005;Beamonte-Barrientos et al 2010), and maternal effects have been shown to alter population robustness in the face of ecological challenges (R€ as€ anen & Kruuk 2007;Kuijper & Hoyle 2015). The maternal condition, for example nutrition availability or disease status, is increasingly recognised to affect offspring susceptibility to infection (Huang & Song 1999;Little et al 2003;Rahman et al 2004;Mitchell & Read 2005;Gasparini et al 2007;Lorenz & Koella 2011;Stjernman & Little 2011;Tidbury et al 2011;Boots & Roberts 2012;Garbutt & Little 2017). This suggests variation in phenotypic traits, as a response to the maternal environment, can drive population and epidemiological dynamics (Beckerman et al 2002;Mitchell & Read 2005;Garbutt et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations have been made in our study species, the crustacean Daphnia magna, where we have observed that increasing maternal age is linked to increasing size at birth, enhanced parasite resistance and changes in reproduction (Clark et al ., ). Variation in maternal nutrition in D. magna appears to produce similar phenotypes, as the offspring of dietary restricted mothers produce relatively large, parasite resistant offspring (Garbutt & Little, ). These increases in body size in offspring from dietary restricted mothers may be adaptive if these mothers can expect their offspring to be born into a low food/high competition environment, and assuming that large offspring have an advantage in this circumstance.…”
Section: Introductionmentioning
confidence: 99%